Statistics in nutrition and dietetics - Nelson, Michael (Nutritionist) (Hoboken, NJ : John Wiley & Sons, 2020)
'As evidence-based practice and research become increasingly important for all health professionals, Statistics in Nutrition and Dietetics provides an easy-to-read introductory textbook written specifically for students on nutrition and dietetics courses. Assuming no prior knowledge and written in a clear, accessible style, it places statistics in the context of nutrition and dietetic practice, making it a vital resource for undergraduate and postgraduate research projects and dissertations and in applying theory and evidence to practice'--
The scientific method -- Populations and samples -- Principles of measurement -- Probability and types of distribution -- Confidence intervals and significance testing -- Two sample comparisons for normal distributions: the t-test -- Non-parametric two-sample tests -- Contingency tables, chi-squared test, and Fisher's Exact Test -- McNemar's test -- Association: correlation and regression -- Analysis of variance -- Design, sample size, and power -- Describing statistical models and selecting appropriate tests -- Designing a research protocol -- Presenting results to different audiences: an introduction
Includes bibliographical references and index.
Keywords: Nutritional Sciences -- statistics & numerical data; Statistics as Topic; Research Design